(untitled) - J. L. Valdés González; U. Solis Cartas; X. P. Manzano Herdoiza (ESPOCH Congresses, 2021)
Abstract Introduction: HIV-AIDS is an infectious disease that damages the immune system, putting you at risk of serious infections and certain types of cancer. Micronutrient deficiency varies widely, depending on the population and stage of the disease. It can contribute to the weakening of the immune state and the worsening of the physical condition. Objective: To identify through the collection of nutritional information the consequences produced by the lack of micronutrients in patients with HIV-AIDS. Methodology: It was carried out through bibliographic reviews, scientific articles in order to find true and proven information on the effect that micronutrient deficiency has on people with HIV/AIDS. Results: It is shown that clinical deficiencies of some nutrients occur rapidly in response to dietary deficiencies, malabsorption, or altered metabolism, while those nutrients that have reserves in the body take longer to deplete. Discussion: The acquired immunodeficiency virus that causes AIDS; is associated with weight loss due to malnutrition. There are foods that can counteract many of the symptoms of the patient with HIV/AIDS, hence the importance of their knowledge. Conclusion: Micronutrient deficiency influences the immune system, accentuating the immunodeficiency that leads to AIDS. People living with this disease should have a balanced diet with Vitamins A, B, zinc and iron to strengthen the immune system, these offer a safe and economical treatment to slow the progression of the infection.